(untitled) - Stein, Kathleen (Hoboken, N.J., 2007)
Veteran popularizer of science and technology Stein reveals the secret bunker of humanness to be in the prefrontal cortex. She looks in turn at the five aspects, then considers silicon minds and the rise of the machine genius. In addition to describing scientific theories and findings in plain English, she explores the research processes that led to them, and provides scenarios demonstrating the different functions.
Keywords: Prefrontal cortex,Prefrontal cortex; Physiology